2014
DOI: 10.1016/j.exer.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine inhibits amyloid-beta induced activation of NF-κB, NLRP3 inflammasome and cytokine production in retinal pigment epithelial cells

Abstract: Chronic inflammation is a key pathogenic process in age-related macular degeneration (AMD). Amyloid-beta (Aβ) is a constituent of AMD drusen and promotes the activation of NLRP3 inflammasome which facilitates the production of cytokines. We investigated the role of transcription factor NF-κB in the activation of inflammasome in the RPE and the effect of vinpocetine, a dietary supplement with inhibitory effect on NF-κB. ARPE19/NF-κB-luciferase reporter cells treated with Aβ demonstrated enhanced NF-κB activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 48 publications
0
76
0
2
Order By: Relevance
“…The activation signal subsequently triggers assembly of NLRP3 and other protein components into the active inflammasome protein complex that results in caspase-1-mediated cleavage of pro-IL-1␤ and pro-IL-18 into mature IL-1␤ and IL-18. Several substances have been suggested to provide the inflammasome activation signal in AMD including drusen components such as C1q (13) and amyloid-␤ (14), Alu RNA accumulation secondary to DICER1 deficiency (8), the lipofuscin component Nretinylidene-N-retinyl-ethanolamine (A2E) (15), and the lipid peroxidation product 4-hydroxynonenal (HNE) (16). We have recently suggested an additional mechanism by demonstrating that photooxidative damage to the RPE, enhanced by accumulated lipofuscin, can activate the NLRP3 inflammasome by inducing lysosomal membrane permeabilization and cytosolic leakage of lysosomal enzymes (17,18).…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…The activation signal subsequently triggers assembly of NLRP3 and other protein components into the active inflammasome protein complex that results in caspase-1-mediated cleavage of pro-IL-1␤ and pro-IL-18 into mature IL-1␤ and IL-18. Several substances have been suggested to provide the inflammasome activation signal in AMD including drusen components such as C1q (13) and amyloid-␤ (14), Alu RNA accumulation secondary to DICER1 deficiency (8), the lipofuscin component Nretinylidene-N-retinyl-ethanolamine (A2E) (15), and the lipid peroxidation product 4-hydroxynonenal (HNE) (16). We have recently suggested an additional mechanism by demonstrating that photooxidative damage to the RPE, enhanced by accumulated lipofuscin, can activate the NLRP3 inflammasome by inducing lysosomal membrane permeabilization and cytosolic leakage of lysosomal enzymes (17,18).…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…40 It has been reported that a single intraocular injection of oligomeric Ab leads to overproduction of inflammatory cytokines and activation of nuclear factor (NF)-jB signaling in the RPE in rats. 38,41 This model may become useful for exploring the potential mechanisms involved in the early phases of AMD. Here, in agreement with Cao et al, 7 we further demonstrated Ab is an inducer of inflammatory responses in human RPE cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…7,38 Briefly, 1 mg lyophilized Ab1-42 or Ab42-1 (reverse peptide) was dissolved in 400 lL 1,1,1,3,3,3-Hexafluoro-2-propanol (HFIP) and incubated overnight at 48C. Of the resulting seedless solution, 100 lL was subjected to a gentle stream of nitrogen for 5 to 10 minutes to evaporate the HFIP and incubated the peptide in 100% dimethyl sulfoxide at 2 mM for 15 minutes at room temperature with periodic vortexing at moderate speed.…”
Section: Preparation Of Ab1-42 Peptidementioning
confidence: 99%
“…Ïðåïàðàò ñíèaeàë óðîâåíü öèòîêèíîâ è â ñòåêëîâèäíîì òåëå. Ïî-âèäè-ìîìó, áëîêàäà ñèñòåìû NF-kÂ, íàáëþäàåìàÿ ïðè ïðè-ìåíåíèè âèíïîöåòèíà, ìîaeåò áûòü ýôôåêòèâíûì ñïî-ñîáîì ïðîôèëàêòèêè è ëå÷åíèÿ ÂÌÄ [41].…”
Section: îáùèå ïðèíöèïû ïðîòèâîâîñïàëèòåëüíîãî äåé-ñòâèÿ êàâèíòîíàunclassified